(untitled) (Research, Society and Development, 2021)
The research presented aims to analyze the impacts on the professional trajectories of the graduates of the Technical Course in Agricultural Integrated to High School of the Technical School Vale da Uva Goethe. Methodologically, this research presents itself as being of an applied nature with a qualitative approach, characterized as descriptive research, with an exploratory dimension. This research was carried out through a case study, based on the work of Yin (2005). Participated in the research graduates of the Technical Course in Agricultural Integrated to High School of the Agricultural Technical School Vale da Uva Goethe. As a data collection instrument, a questionnaire composed of interpersonal questions was applied, listing the main contexts of the course structure and its importance for graduates. Expectations of graduates regarding the course were identified, valuing their experiences. In general, the impact of the course was highly relevant and positive in his academic and professional life. The level and intensity of the impact of the course on the graduates’ lives are different, because the experiences and experiences of each subject are also different. Thus, this diversity favored the exchange of experiences among students, adding new knowledge and reflecting on the impacts provided by the technical course.